Reduced peanut sensitization with maternal peanut consumption and early peanut introduction while breastfeeding. (9th October 2021) - Azad, Meghan B.; Dharma, Christoffer; Simons, Elinor; Tran, Maxwell; Reyna, Myrtha E.; Dai, Ruixue; Becker, Allan B.; Marshall, Jean; Mandhane, Piushkumar J.; Turvey, Stuart E.; Moraes, Theo J.; Lefebvre, Diana L.; et al.
Abstract: New guidelines for peanut allergy prevention in high-risk infants recommend introducing peanut during infancy but do not address breastfeeding or maternal peanut consumption. We assessed the independent and combined association of these factors with peanut sensitization in the general population CHILD birth cohort ( N = 2759 mother–child dyads). Mothers reported peanut consumption during pregnancy, timing of first infant peanut consumption, and length of breastfeeding duration. Child peanut sensitization was determined by skin prick testing at 1, 3, and 5 years. Overall, 69% of mothers regularly consumed peanuts and 36% of infants were fed peanut in the first year (20% while breastfeeding and 16% after breastfeeding cessation). Infants who were introduced to peanut early (before 1 year) after breastfeeding cessation had a 66% reduced risk of sensitization at 5 years compared to those who were not (1.9% vs. 5.8% sensitization; aOR 0.34, 95% CI 0.14–0.68). This risk was further reduced if mothers introduced peanut early while breastfeeding and regularly consumed peanut themselves (0.3% sensitization; aOR 0.07, 0.01–0.25). In longitudinal analyses, these associations were driven by a higher odds of outgrowing early sensitization and a lower odds of late-onset sensitization. There was no apparent benefit (or harm) from maternal peanut consumption without breastfeeding. Taken together, these results suggest the combination of maternal peanut consumption and breastfeeding at the time of peanut introduction during infancy may help to decrease the risk of peanut sensitization. Mechanistic and clinical intervention studies are needed to confirm and understand this "triple exposure" hypothesis.